Analisis Kebutuhan Tenaga Instalasi Rekam Medis Berdasarkan Analisis Beban Kerja Dengan Metode WISN - Mayliza Da Nerra Carunie Jatmiko; Febria Listina; Dian Utama Pratiwi Putri (PT.Mantaya Idea Batara, 2024)
Workload is an essential component in calculating energy requirements. The Workload Indicators of Staffing Need method is a method for calculating energy requirements based on the actual workload carried out by the workforce. This research aims to determine the description of labor needs in the Medical Records Installation using work sampling techniques and then use this to calculate labor requirements. This research was conducted at the Medical Records Installation of the Lampung Province Regional Mental Hospital for 8 days. This research uses a qualitative approach by conducting observations and in-depth interviews. The research results showed that calculating the number of staffing needs using the Workload Indicators of Staffing Need method showed that the registration section was 4.8 people, the inpatient registration section was 0.5 people, the analysis section was 0.5, the coding section was 1.0 people, the reporting section was 3.7 people, filling requires 6.0 people, emergency room registration 1.1 people, the needed total staff is 18 people to adjust the workload, so that departments experiencing delays can complete their work. From the results of this research, it is recommended that the management of the Lampung Province Regional Mental Hospital consider adding 6 officers to suit the workload so that delays in completing tasks at the medical records installation can be resolved.